(untitled) - L O van Reeuwijk (Rome, Italy, 1998)
This book introduces a number of basic measures to be adopted in a laboratory regarding, standard operating procedures, organization and personnel, facilities and safety, equipment and working materials, analytical or testing systems and basic statistical tools, quality control and reporting and filling of results
Keywords: plant-soil relationships,soil science